Parent-report health-related quality of life in school-aged children with cerebral palsy: A cross-sectional study - Vila-Nova, Fábio; Santos, Sofia; Oliveira, Raul; Cordovil, Rita (Frontiers in Rehabilitation Sciences, 2022)
Quality of life is both a goal and an outcome in Cerebral Palsy (CP) rehabilitation. Children with CP may show impaired health-related quality of life (HRQoL) compared to their typical peers. Parents' perceptions of HRQoL of their children could help rehabilitation professionals to identify areas for intervention aiming to improve health and wellbeing. This study aims to compare the proxy HRQoL of Portuguese school-aged children with CP and the general population, and to analyze child and family correlation. Differences were examined using European normative data for children from 8 to 18 years. Correlation and regression analysis examined the association between child and family variables in the CP group with statistically significant low scores. Sixty-eight parents of children and adolescents with CP (12.5 ± 2.91 years) answered the KIDSCREEN-52 parent version. We identified clinically significantly lower HRQoL in four out of ten HRQoL domains (Physical well-being, Autonomy, Moods & Emotions, and Bullying) than the norm peers. Correlations were found between the number of siblings and Autonomy (r = .315), meaning that having more siblings was associated with greater autonomy, and between mobility and Moods & Emotions (r = −.261), where children with impaired mobility shown low scores as perceived by their parents. Age, sex, mobility and cognitive impairment explained 32% of Physical well-being scores (p < .001). Mobility and cognitive impairment explained 16% of Bullying scores (p = .001). Although the family and child variables identified in this study are non-modifiable, they can help in the identification and early intervention aimed at improving HRQoL. Rehabilitation professionals should assess parent perceptions, extending the HRQoL assessment to children who can report and other informants, aiming at fostering wellbeing in children and adolescents with CP.